A Rare Cause of Hemophagocytic Lymphohistiocytosis: Fusobacterium Infection—A Case Report and Review of the Literature - Ghulam Rehman Mohyuddin; Heather J. Male (Case Reports in Hematology)
Hemophagocytic lymphohistiocytosis (HLH) is a rare syndrome characterized by excessive activation of the immune system. Bacterial infections are very rare precipitants of this disease. A 19-year-old gentleman presented with headache, fatigue, and malaise. He was found to be hypotensive, tachycardic, and febrile. Broad spectrum antibiotics were initiated, and a lumbar puncture ruled out meningitis. Patient progressively developed shock that required use of vasopressors, as well as renal and respiratory failure. Blood cultures grew Fusobacterium necrophorum. Given continued fevers despite appropriate antimicrobials, a bone marrow biopsy was performed revealing increased histiocytes with hemophagocytosis. Dexamethasone was added with dramatic clinical improvement. Our case highlights Fusobacterium as a rare precipitant of HLH and proves that a high index of clinical suspicion is crucial for early diagnosis of HLH, allowing for prompt initiation of HLH-specific immunosuppressive therapy that can be life-saving.